Remove me from this list: A case study of trolling in an academic mass email thread - Chen, Yimin (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2019)
This work examines in detail trolling behaviour that occurred during the mass email “reply allpocalypse” of 2019 at a university in southwestern Ontario. Whereas internet trolling is generally thought of as anonymous, antisocial behaviour, this event defies such characterizations in three ways: 1) all respondents participated on a real-name basis, 2) the majority of trolling messages sent were non-malicious attempts at humour, and 3) the email trolling seemed to have at least some pro-social, community-building effects. This study challenges assumptions about who engages in internet trolling and for what purpose by presenting an example of benign trolling in academia.